Nursing Students' Migration Intentions: A Comparative Study of Türkiye and The Philippines - Cemre Karatiken; Gulcan Bagcivan; Ruhat Tilki; Ayise Karadag (KHD-Production, 2024)
This study aims to determine the migration intention of nursing students and the factors affecting it in Türkiye and the Philippines. A total of 284 nursing students were included in this descriptive study. The